Roll-to-roll processing of film substrates for hybrid integrated flexible electronics. (21st February 2018) - Palavesam, Nagarajan; Marin, Sonia; Hemmetzberger, Dieter; Landesberger, Christof; Bock, Karlheinz; Kutter, Christoph
Abstract: Roll-to-roll (R2R) processing on film substrates has been demonstrated to have the potential for achieving high throughput manufacturing of organic electronic systems at low cost. However, the ever-growing mobile devices market accompanied by the developments in information and communication technologies require high performance systems at very low power operation, sometimes on larger substrates having sizes in the range of a few metres. Organic electronics often fall short of fulfilling the required computing performance and power requirements of most of the common use cases. Hybrid integration of inorganic monocrystalline silicon chips on polymer films is a means to fulfil the aforementioned requirements. In this context, it is opportune to report our recent activities on R2R processing of plastic films for hybrid integration of flexible electronics. Hybrid integration can be performed with conventional, rigid surface mount devices as well as flexible, ultra-thin bare silicon chips. The first section of the paper is dedicated to a brief overview of R2R manufacturing of electronic devices with an example of production of radio frequency identification tags as well as to a discussion emphasising the targets for hybrid integration. Then, detailed descriptions about our processes for R2R manufacturing of metal wiring lines on films and hybrid integration are included. Three-dimensional integration of films and a temperature sensor label manufactured using hybrid integration process are also elaborated on. Furthermore, key results from fatigue reliability assessment of R2R metallised wiring lines are reported. Finally, some of the challenges in transferring the R2R processes for hybrid integration on film substrates from research labs to industrial manufacturing are highlighted.